Evaluating the effects of water matrix constituents on micropollutant removal by activated carbon and β-cyclodextrin polymer adsorbents. (15th April 2020) - Ling, Yuhan; Alzate-Sánchez, Diego M.; Klemes, Max J.; Dichtel, William R.; Helbling, Damian E.
Abstract: The performance of adsorbents for the removal of organic micropollutants (MPs) from water can be influenced by the presence of water matrix constituents. The objective of this research was to evaluate the influence of water matrix constituents on the performance of coconut-shell activated carbon (CCAC), porous β-cyclodextrin polymer (CDP), and CDP coated on cellulose microcrystal (CDP@CMC) adsorbents. MP removals were measured in batch experiments for a mixture of 90 MP at 1 μg L −1 and MP breakthrough was measured in rapid small-scale column test (RSSCT) experiments for a mixture of 15 MP at 500 ng L −1 . All experiments were performed first with nanopure water, and subsequently with six different water samples collected from two separate groundwater, surface water, and wastewater effluent sources. The results of batch and RSSCT experiments demonstrate more rapid adsorption kinetics and less adsorption inhibition in the presence of matrix constituents for CDP adsorbents relative to CCAC. Further, the treatment capacity of CDP@CMC in the RSSCT experiments was higher than that of CCAC, particularly in more complex water matrices. Statistical analyses were performed to investigate associations between adsorption inhibition among groups of MPs and the concentrations of specific water matrix constituents. For CCAC, adsorption inhibition was observed for all MPs and was primarily attributed to the presence of dissolved organic matter with molar weight less than 1000 Da. For CDP adsorbents, adsorption inhibition was primarily observed for cationic MPs and was attributed to the screening of the negative surface charge of CDP by inorganic ions in water samples with high ionic strength. These data further demonstrate the value of CDP as an alternative adsorbent to CCAC for the removal of MPs during water and wastewater treatment. Graphical abstract: Image 1 Highlights: Water samples from different sources characterized for water matrix constituents. Micropollutant removal measured in laboratory-scale batch adsorption experiments. Micropollutant breakthrough measured in rapid small-scale column test experiments. β-cyclodextrin polymers exhibit less adsorption inhibition than activated carbon. Inorganic ions and dissolved organic matter contribute to adsorption inhibition.